Linguistic signs and means of expression in the subjective nature of conflic (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
This article describes the representation of verbal markers in interpersonal conflict, based on the reactions of the person and the link between the development of conflicts and feelings of a man were identified, the author also based Ukranian linquistics and cultural causes in political conflicts.
Keywords: interpersonal conflict of subjective nature; the linguistic features of the conflict; the means of expression of the conflict; political conflict